Modulation of the Vitis vinifera cv. ‘Chardonnay’ microRNA and mRNA transcriptomes in response to aster yellows phytoplasma-infection - Snyman, Marius Christian (Stellenbosch : Stellenbosch University, 2019)
Thesis (PhDAgric)--Stellenbosch University, 2019.